Concentration level of heavy metals in soil at vegetables areas in Kota Bharu, Kelantan, Malaysia - Abdul Rahman, Haliza; Zaim, Farah Adhila (International Journal of Environmental Science and Development, 2015)
The study was focused on heavy metals which are copper (Cu), zinc (Zn) and lead (Pb) that are known as the most toxic and poisonous to human health. The objectives of this research was to determine, analysis and compare the heavy metal concentration level in two study areas at Kg. Kubang Edang, Peringat and Kg. Tok Kambing, Sering, both are in Kota Bharu, Kelantan, Malaysia. The result obtained in the soil samples of Kg. Kubang Edang shows that Pb concentration has highest concentration of heavy metals with 7.396 mg/L followed by Zn, 7.077 mg/L and Cu has the lowest concentration with 3.705 mg/L. On the other hand, the result obtained in the soil samples of Kg. Tok Kambing shows that Pb has the highest concentration with 11.304 mg/L followed by Zn with concentration level of 10.667 mg/l and Cu has the lowest concentration with 4.576 mg/L. The result shows heavy metals concentration level in Kg. Tok Kambing was higher as compared to Kg. Kubang Edang. Analyzing the data using parametric T-test shows that, there were significant differences of heavy metals concentration level in two study areas with p-value <0.05.